In Vitro – In Vivo Evaluation of Okra Gum: Guar Gum Compression Coated Diclofenac Sodium Tablets for Colonic Delivery: A Factorial Approach - Kotadiya, R M (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTColon targeting would be valuable when a delay in absorption is therapeutically desirable in treatment of chronic medical condition like rheumatoid arthritis (RA). The major objective was to modulate drug release of prepared matrices to target the peak symptoms of RA in early morning. The main interest in such dosage form was to target the drug to the colon by ensuring minimal amount of drug release in the physiological environment of the upper GI tract. Preparation of compressed coated tablets was done using okra gum and guar gum followed by optimization using 32 full factorial designs. Tablets were evaluated for in vitro characterizations including detailed dissolution study, in vivo pharmacokinetic study and stability study. Formulation (F9) of okra gum: guar gum in 75:25 % ratios with 450mg coat weight is most likely to provide colonic delivery Diclofenac sodium. In vivo ingestion in rabbits showed controlled release pharmacokinetic profile of prepared formulation (F9) with Cmax of 22.31 mcg/mL at 6h (Tmax) compare to marketed formulation (voveran) with Cmax of 23.64 mcg/mL at 2h (Tmax). The insignificant changes in the physical appearance, drug content and dissolution profile of F9 formulation after storage at 400 C/75% RH for 3 months indicate good stability.